Acute Diverticulitis in the Young: The Same Disease in a Different Patient - Adolfo Pisanu; Valentina Vacca; Isabella Reccia; Mauro Podda; Alessandro Uccheddu (Gastroenterology Research and Practice)
Background. Natural history and risk factors for diverticulitis in young patients are still debatable. This study aimed to assess whether difference exists in patients aged 50 and younger when compared to older patients and to identify risk factors for acute diverticulitis in the young. Patients and Methods. From January 2006 to December 2011, 80 patients were admitted to our department for acute diverticulitis. We carried out a cross-sectional study in 23 patients (28.7%) aged 50 and younger and 57 older patients (71.3%). Results. Acute diverticulitis in the young was not more aggressive than in the older patient. Diverticulitis at patient’s admission was similar with respect to Hinchey’s stage and prior history of diverticulitis. No significant difference was found for both medical and surgical treatment. The rate of recurrent diverticulitis in nonoperated patients was similar. Male gender, body mass index ≥25, and assumption of alcohol were independent risk factors for the occurrence of an acute diverticulitis in the young. Conclusions. The same disease seems to be affecting young patients such as overweight or obese male individual. Current policies to prevent diverticular disease and its related complications must include obesity control together with high-fiber diet and regular exercise.